Математическое описание динамического поведения ротора в магнитных подшипниках в зависимости от принятых упрощений. Часть 1. Жесткий ротор - Мартыненко, Геннадий Юрьевич (НТУ "ХПИ", 2009)
У роботі запропоновано формування математичної моделі ротора в магнітних підшипниках різних типів. Моделювання проводиться на основі диференціальних рівнянь Лагранжа другого роду і рівнянь Максвела, наведено і обґрунтовано варіанти математичних моделей, які записані при різних припущеннях і обмеженнях.

In work, forming of mathematical model of rotor on magnetic bearings of different types is offered. The design on the basis of Lagrange differential equations the second kind and equations of Maxwell is performed. There are represented and grounded variants of mathematical models in the work. The models are written down for different suppositions and limitations.
Keywords: магнитный подвес; постоянные магниты; электромагнитные резонансные подшипники; упруго-демпферные опоры; магнитные поля